Dissecting the role of NtrC and RpoN in the expression of assimilatory nitrate and nitrite reductases in Bradyrhizobium diazoefficiens - López, María Florencia (2017)
Bradyrhizobium diazoefficiens, a nitrogen- fixing endosymbiont of soybeans, is a model strain for studying rhizobial denitrification. This bacterium can also use nitrate as the sole nitrogen (N) source during aerobic growth by inducing an assimilatory nitrate reductase encoded by nasC located within the narK-bjgb-flp-nasC operon along with a nitrite reductase encoded by nirA at a different chromosomal locus. The global nitrogen two-component regulatory system NtrBC has been reported to coordinate the expression of key enzymes in nitrogen metabolism in several bacteria. In this study, we demonstrate that disruption of ntrC caused a growth defect in B. diazoefficiens cells in the presence of nitrate or nitrite as the sole N source and a decreased activity of the nitrate and nitrite reductase enzymes. Furthermore, the expression of narK-lacZor nirA-lacZ transcriptional fusions was significantly reduced in the ntrC mutant after incubation under nitrate assimilation conditions. AB. diazoefficiens rpoN 1/2 mutant, lacking both copies of the gene encoding the alternative sigma factor σ54, was also defective in aerobic growth with nitrate as the N source as well as in nitrate and nitrite reductase expression. These results demonstrate that the NtrC regulator is required for expression of the B. diazoefficiens nasC and nirA genes and that the sigma factor RpoN is also involved in this regulation.